Carbapenemase-producing organism (CPO) colonisation at a district general hospital: universal screening may help reduce transmission. Issue 3 (September 2021) - Phee, Lynette; Paget, Stephanie; Jacques, Judy; Bharathan, Binutha; El-Mugamar, Husam; Sivaramakrishnan, Anand
Summary: Objective: Assess the potential of hospital-wide routine screening by determining the prevalence and incidence of carbapenemase-producing organisms (CPOs) isolated from rectal screens at Barnet and Chase Farm Hospitals. Methods: 3, 553 samples were collected between 01/12/2018 and 31/08/2019: from adult critical care wards (universal screening - admission, discharge and weekly), from medical wards with risk-factor based screening according to the prevailing Public Health England (PHE) carbapenemase-producing Enterobacteriaceae (CPE) screening guidelines, or on an ad hoc basis. Prevalence was defined as previously documented positive CPO colonisation, or new positive status, as a proportion of all eligible samples. Incidence was defined as all newly positive patients per 1, 000 patient-days. Results: Overall CPO prevalence was 2.1% (95% CI: 1.61–2.58%). Inpatient prevalence was significantly higher at 2.6% vs outpatient at 0.5% ( p < 0.001). Incidence was 0.44 per 1, 000 patient-days (95% CI: 0.33–0.57), with a rate ratio between Barnet and Chase Farm of 4.9 ( p  = 0.013). Incidence was highest where universal screening strategy was applied (3.9 per 1000 patient-days, 95% CI: 2.4–5.91). This was 2.5 times higher than risk-factor based screening ( p  = 0.005) and 23.5 times that of wards without routine surveillance implemented ( p < 0.001). Conclusion: Surveillance remains a cornerstone in controlling CPO transmission. Our local incidence, lacking hospital-wide screening, significantly exceeded the reported UK average. Universal screening could help to uncover the true prevalence and incidence of CPO, thereby providing the necessary information to properly control transmission, reducing nosocomial outbreaks and ultimately reducing the overall cost to healthcare.